PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KOPI DI KECAMATAN ULU BELU KABUPATEN TANGGAMUS - Maylani Florensi Hutasoit; Fembriarty Erry Prasmatiwi; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
The purpose of this study is to analyse household income and welfare of coffee farmers. This research was conducted in two villages, i.e. Ngarip Village and Sukamaju Village in Ulu Belu Subdistrict, Tanggamus Regency. The sampling used is a systematic random sampling with total samples of 38 farmers taken proportionally from each village. This research was conducted in April-June 2017. The research method is a survey method with quantitative analysis method. The results showed that the average income of farmers is Rp37,28,118.44 per year. According to Sajogyo expenditure indicator, the welfare of farmers is in a decent enough category, and according to Statistics Bureau (BPS) 2015 indicator, farmers' welfare is in high category.Key words: expenditure, income, welfare